2014
DOI: 10.3103/s1067821214030079
|View full text |Cite
|
Sign up to set email alerts
|

Sugar industry fly ash: an additive for molding sand to make aluminium castings

Abstract: X ray diffraction, thermogravimetric analysis, scanning electron microscopy and energy disper sive spectroscopy studies were performed with molding sand and sugar industry fly ash to evaluate and com pare their physical properties. We noted that several physical properties of sugar industry fly ash and molding sand were similar. We then tested the permeability, green compression strength and dry compression strength of various compositions of sugar industry fly ash and bentonite to explore their potential as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…The effect of bentonite clay and fly ash on sand mould property is shown in Fig. 1 [56]. It is observed that the mould permeability and strength decrease as the concentration (wt%) of sugar industry fly ash increases in moulding sand.…”
Section: Fly Ashmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of bentonite clay and fly ash on sand mould property is shown in Fig. 1 [56]. It is observed that the mould permeability and strength decrease as the concentration (wt%) of sugar industry fly ash increases in moulding sand.…”
Section: Fly Ashmentioning
confidence: 97%
“…Sugar industries produce fly ash by burning the sugarcane bagasse [56]. The effect of bentonite clay and fly ash on sand mould property is shown in Fig.…”
Section: Fly Ashmentioning
confidence: 99%
“…Single zone model assumes the charge as homogeneous and single wiebe heat release model is widely used to model SI combustion. Here we use two wiebe model as we are simulating a Direct Injection Diesel Engine [37][38][39][40][41]. Heat transfer by convection from gas to the cylinder walls or from the cylinder walls to the gas is considered over the entire cycle.…”
Section: Fig:7 -Data Input Window For Engine Geometrymentioning
confidence: 99%
“…The luminaire is a fixture used in the manufacturing industry. It is used to attach accessories (placement in a specific location or orientation) and to support the work [32][33][34][35][36]. Improving the efficiency of production by simplifying ducing the need for skilled labour and increasing the compatibility of workers in production.…”
Section: Fixturementioning
confidence: 99%